The severity of anxiety and depression in women in the postpartum period and mother-child interaction - A. G. Koshchavtsev; V. V. Pozdnyak; S. V. Grechanyi (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
The purpose of the study was to study the relationship of quantitative indicators of anxiety and depression in women in the postpartum period with the types of mother-child interaction. The main group consisted of 93 women in the postpartum period with a total score on the Beck Depression Self-Assessment Inventory (BDI) of 10 or higher. The comparison group consisted of 33 women with a total BDI score of 9 points or less. Double testing using the Spielberger Personal and Situational Anxiety Scale (STAI) was carried out on days 5-7 of admission and 1 week after the initial testing. The questionnaire of maternal selfassessment of interaction with the child (MSIR) and the method of objective assessment of maternal-child interaction (OMDV) from 7 to 15 days of stay were used. The results showed that in the absence of age differences and length of stay in the hospital, those examined, whose total BDI score was 10 or more, had significantly higher values of personal and situational anxiety during the initial and repeated examinations. The value of the HRMS score was also significantly higher in the main group, which indicates that mothers with high rates of depression tend to underestimate the level of their interaction with the child, are more selfcritical about the ability to understand the newborn and the skills of educational competence. The dynamics of personal and situational anxiety revealed a significant decrease in the main group and the comparison group, which indicates a reduction in the intensity of affective experiences. In the main group, the number of women with a formal type of mother-child interactions significantly prevailed, and in the comparison group - with a harmonious type. Thus, the experience of women in the postpartum period with BDI values of 10 and above of insufficient “maternal competence” is a consequence not only of a high level of self-criticism, but also of objective difficulties in interacting with the child, which indirectly confirms the positive role of pediatric patronage and psychosocial support in the treatment of postpartum affective disorders. experiences